Application of SAVI Learning Model to Improve Students' Arabic Learning Outcomes - Fakhrin, Nurul; Wahdi, Rifana; Akmal, Dinul (Universitas Muhammadiyah Sumatera Barat, 2023)
The SAVI-based e-module model as an improvment, maintenance and enrichment of the Arabic language learning process at SMPIT, is able to overcome the problems of low motivation, difficulty retaining material, low skills, and increase student learning achievement. The purpose of this study was to determine the effect of the application of SAVI learning model on Arabic learning outcomes of Mutiara Quran Solok Junior High School students.. The research method uses quasi-experimental research. The independent variable is the SAVI learning model and the dependent variable is Arabic learning outcomes. The author's sampling technique used a total sampling technique, namely all 19 class VIII students as the experimental class. The results of data analysis obtained a value (2-tail 0.05, namely 0.003 0.05) which can be concluded that the application of the SAVI learning model has a significant influence on the Arabic learning outcomes for class VIII SMPIT Mutiara Quran Solok students in Solok. This states that there is an increase in students' Arabic learning outcomes when the SAVI learning model is applied.